2022
DOI: 10.3390/e24050688
|View full text |Cite
|
Sign up to set email alerts
|

Heuristic Optimization of Deep and Shallow Classifiers: An Application for Electroencephalogram Cyclic Alternating Pattern Detection

Abstract: Methodologies for automatic non-rapid eye movement and cyclic alternating pattern analysis were proposed to examine the signal from one electroencephalogram monopolar derivation for the A phase, cyclic alternating pattern cycles, and cyclic alternating pattern rate assessments. A population composed of subjects free of neurological disorders and subjects diagnosed with sleep-disordered breathing was studied. Parallel classifications were performed for non-rapid eye movement and A phase estimations, examining a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…The results indicated that using features improved performance, likely because the limited data did not allow the deep learning model to learn all relevant characteristics. These features were later used by Mendonça et al [ 65 ] that conducted a similar analysis but proposed the Heuristic Oriented Search Algorithm (HOSA) for optimizing the structure of deep learning models. The authors examined the performance of LSTM fead with features agains the LSTM fead with the preprocessed EEG signal, and concluded again that the use of the feature-based model was superior for the same reason as previously stated.…”
Section: Resultsmentioning
confidence: 99%
“…The results indicated that using features improved performance, likely because the limited data did not allow the deep learning model to learn all relevant characteristics. These features were later used by Mendonça et al [ 65 ] that conducted a similar analysis but proposed the Heuristic Oriented Search Algorithm (HOSA) for optimizing the structure of deep learning models. The authors examined the performance of LSTM fead with features agains the LSTM fead with the preprocessed EEG signal, and concluded again that the use of the feature-based model was superior for the same reason as previously stated.…”
Section: Resultsmentioning
confidence: 99%
“…For the prediction of the axial IOL equator plane position (as a scalar parameter), a simple univariate model is sufficient. We implemented 2 different models for each prediction: First, we set up a shallow feedforward neural network [ 20 , 30 ], and second, we implemented a multilinear regression model (bivariate for decentration and tilt and univariate for axial IOL equator position) as a reference [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…the optimisation was performed in terms of minimising the mean squared prediction error, which refers to a metric for the performance of the prediction [ 20 ]: …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation